The effect of nutritional status and TNF alpha to lung function on marble craftsman - Widajati, Noeroel; Tiara, Nisrina; Martiana, Tri; Mohd Elias, Saliza; Priyandani, Yuni (Penerbit UTM Press, 2024)
Marble craftsmen are potentially exposed to marble dust which contains about 60% silica resulting in marble craftsmen facing this hazard and possibly physiological lung disorders. This study aims to analyze the effect of working period, nutritional status, and TNF-α on physiological lung disorders. study is a quantitative study with observational research type and cross sectional research design In this study, the data collection techniques used were: (1) measurement of personal dust levels using a personal CCZG2A type; (2) TNF-α levels using the ELISA technique, (3) lung function with MIR spirolab III; (4) collection of data on respiratory complaints using the ATS standard questionnaire. (5) measurement of nutritional status by weighing body weight and measuring height. The subjects of this study were all marble craftsmen who worked in the marble household industry in Tulungagung Regency as many as 30 people with the number of samples taken as many as 26 craftsmen. The average value of %FVC in obese respondents was lower than that of respondents with normal nutritional status. The results of linear regression analysis showed that the respondents' working period had a significant effect (p=0.003) on serum TNF-α levels, with a value of p≤0.05. Serum TNF-α levels also had a significant effect on FEV1 and FVC (FEV1 p=0.007; FVC p=0.008), and nutritional status also had a significant effect on FVC (p=0.05, β=0.02). The greater a person's body weight, the faster the breathing frequency, so that more dust enters the respiratory air.